Stemming "commercial" illicit financial flows & developing country innovations in the global tax reform agenda - Manuel F. Montes; Daniel Uribe; Danish (South Centre, 2018)
Illicit Financial Flows generated due to the commercial activities of multinational enterprises are quantitatively the most important challenge faced by developing countries in achieving the Sustainable Development Goals. Current efforts for stemming these illicit flows and reforming the international tax system are however being led by developed countries, with developing country interests poorly reflected in the reform agenda. This research paper highlights the tax issues of great priority for developing countries and how international tax cooperation can contribute to preventing such illicit flows.
Keywords: 300; Kapitalmobilität; Kapitalflucht; Steuerflucht; Internationales Steuerrecht; Welt